AKUNTABILITAS PENGELOLAAN KEUANGAN MASJID MELALUI PENDEKATAN FENOMENOLOGI (STUDI EMPIRIS DI MASJID AGUNG SIDIKALANG) - Wahyu Ansahrizal; Abidin Alimuddin Sihotang (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2023)
This study aims to show the importance of accountability in financial reporting at the Great Mosque of Sidikalang. This study uses a qualitative descriptive method with a phenomenological approach. There is a phenomenological approach available to learn more about the activities and finances contained in the Great Mosque of Sidikalang. The results of this study indicate that accountability in managing finances at the Great Mosque of Sidikalang is structured by upholding the values of trust, sincerity, responsibility, and cooperation to be accountable to Allah SWT and the Ummah. The financial reports at the Great Mosque of Sidikalang are not in accordance with PSAK No. 45 and only present simple reports, namely expenses and expenses. Therefore, researchers construct mosque financial reports that are in accordance with PSAK No. 45 of the obtained data.